Value-Based Humanism: The Dynamics of Religion in Education Towards a Civil Society - Rohendi, Leon; Rahim, Rahimin Affandi Abdul (UIN Sunan Gunung Djati Bandung, 2024)
This research explores the potential of religious education as a key to forming an inclusive, just and empowered civil society. Involving a holistic approach with qualitative research methods, the findings highlight that religious education should not only focus on the transfer of religious knowledge but should also stimulate students' critical thinking and active participation. The concept of inclusivity was identified as a crucial foundation, with recognition and respect for diversity of beliefs as an important element. The goal is to create a social climate that supports harmony and mutual understanding in a diverse society. The results of this research have significant implications for designing educational policies that integrate the values of inclusivity and active participation into religious curricula. Teachers are identified as key players and need to be empowered as dialogue facilitators who are able to guide students in a deep learning process. Teacher training programs are also proposed to ensure that the values of inclusivity and appreciation of differences are effectively integrated into religious education. By combining these concepts, this research builds a solid foundation for civil society. Holistic and inclusive religious education is considered a catalyst for positive change, opening the door to a just, harmonious and empowered society. By making religious education the main pillar, efforts to form civil society can be more focused and sustainable.